PENGARUH JARAK TANAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays saccharata, Sturt) - Acep Khatin Nuryadin; ENDANG SUPRAPTI; AGUS BUDIYONO (JURNAL ILMIAH AGRINECA, 2016)
The Research is proposed to determine the effect of planting time and dose fertilizer NPK on the growth and yield of seet corn. The research started from July – September 2011, in Village Slatri, Larangan, Brebes Central Java, with altitude 25 m above sea level, alluvial soil type. The research was used factorial in Randomized completely block design (RCBD) with 9 combinations and 3 replications. The treatment is J1P1; Planting time 70 x 20 cm with a dose of 100 kg NPK / ha, J1P2; Planting time 70 x 20 cm with a dose of NPK fertilizer 200 kg / ha, J1P3; Planting time 70 x 20 cm with a dose of NPK fertilizer 300 kg / ha, J2P1; Planting time 70 x 30 cm with a dose of NPK fertilizer 100 kg / ha, J2P2; Planting time 70 x 30 cm with a dose of NPK fertilizer 200 kg / ha, J2P3; Planting time 70 x 40 cm with a dose of NPK fertilizer 300 kg / ha, J3P1; Planting time 70 x 40 cm with a dose of NPK fertilizer 100 kg / ha, J3P2; Planting time 70 x 40 cm with a dose of NPK fertilizer 200 kg / ha, J3P3; Planting time 70 x 40 cm with a dose of fertilizer 300 kg NPK / ha. The results showed that the Planting time of 70 x 40 cm and the use of NPK fertilizer gave the best growth compared with other treatments.